Effect of sugar palm nanofibrillated cellulose concentrations on morphological, mechanical and physical properties of biodegradable films based on agro-waste sugar palm (Arenga pinnata (Wurmb.) Merr) starch - Ilyas R.A.; Sapuan S.M.; Ibrahim R.; Abral H.; Ishak M.R.; Zainudin E.S.; Atikah M.S.N.; Mohd Nurazzi N.; Atiqah A.; Ansari M.N.M.; Syafri E.; Asrofi M.; et al. (Elsevier Editora Ltda, 2023)
Agricultural robots; Agriculture; Cellulose; Cellulose nanocrystals; Elastic moduli; Hydrogen bonds; Mechanical properties; Nanocomposites; Starch; Tensile strength; Agricultural industries; Agro-industrial residue; Agro-wastes; Biodegradable film; High-pressure homogenisation; Intermolecular hydrogen bonds; Mechanical and physical properties; Nanofibrillated cellulose; Sugar industry; Agriculture; Cellulose; Hydrogen Bonds; Mechanical Properties; Starch; Tensile Strength